2009
DOI: 10.1016/j.tet.2009.06.118
|View full text |Cite|
|
Sign up to set email alerts
|

Solvent-dependent oxidative coupling of 1-aryl-1,3-dicarbonyls and styrene

Abstract: This report describes the scope and mechanism of the solvent-dependent, chemoselective oxidative coupling of 1-aryl-1,3-dicarbonyls with styrene using Ce(IV) reagents. Dihydrofuran derivatives are obtained when reactions are performed in methanol whereas α-tetralones can be selectively synthesized in acetonitrile and methylene chloride. Mechanistic studies are consistent with the rate of solvent-assisted deprotonation of a radical cation intermediate playing an integral role in the selective formation of produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Nevertheless, Yoon has recently demonstrated that the counterion can exert a remarkable impact on the observed rate of radical reactions promoted by photoredox catalysts [55] . Usually, the chemoselectivity between dihydrofuran and β,γ‐unsaturated ketone formation was described as dependent on the solvent, [9a,50b,56] the metal oxidant [57] or on the additive [58] . However, Lei observed that different halides have distinct effects on the copper‐mediated redox processes leading to dihydrofurans [13c,59] .…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, Yoon has recently demonstrated that the counterion can exert a remarkable impact on the observed rate of radical reactions promoted by photoredox catalysts [55] . Usually, the chemoselectivity between dihydrofuran and β,γ‐unsaturated ketone formation was described as dependent on the solvent, [9a,50b,56] the metal oxidant [57] or on the additive [58] . However, Lei observed that different halides have distinct effects on the copper‐mediated redox processes leading to dihydrofurans [13c,59] .…”
Section: Resultsmentioning
confidence: 99%
“…Potential side reactions of aryl ketone‐containing 1,3‐dicarbonyls would be the formation of α‐tetralones or 1‐naphthols ( via overoxidation) resulting from CC bond formation through the addition of a cationic ( A ) or radical ( A′ ) intermediate to the phenyl ring (Scheme a, path b). Indeed, the Flowers group reported a solvent‐dependent, Ce(IV)‐mediated oxidative coupling/annulation of 1‐aryl‐1,3‐dicarbonyls with styrene to afford a mixture of α‐tetralones and dihydrofurans with moderate to good selectivities (Scheme b) 1e. α‐Tetralones have been also synthesized by a related Mn(III)‐mediated reaction of aryl methyl ketone with olefins (Scheme c) 3.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, a control experiment in the absence of Ag 2 O confirmed that Ag 2 O is essential for this transformation (entry 14). It should be noted that neither the possible by‐product α‐tetralone (or 1‐naphthol) derivative nor the corresponding fully unsaturated furan was observed in all cases 1e. Optimal reaction conditions were finally established as entry 10 in Table 1 and consisted of 5 mol% In(OTf) 3 and 2 equiv.…”
Section: Methodsmentioning
confidence: 99%
“…In CH 3 OH, the radical cation underwent deprotonation, and after bond rotation/ electron transfer, yielded a dihydrofuran (Scheme 23). 54 Jahn and coworkers have developed a clever method for the synthesis of N,3,4trisubstituted pyrrolidines using a ferrocene-mediated oxidation of enolates as illustrated in Scheme 24. 55 A classic means of generating radicals under reducing conditions involves the use of SmI 2 .…”
Section: Carbon-centered Radical Additions/cyclizationsmentioning
confidence: 99%